Vitamin D Binding Protein (VDBP) and Its Gene Polymorphisms—The Risk of Malignant Tumors and Other Diseases - Rozmus, Dominika (Int J Mol Sci, 2020)
Vitamin D is an important component of the endocrine system that controls calcium homeostasis and bone mineralization. Because of the very short half-life of free serum vitamin D it is stabilized and transported to target tissues by being bound to the vitamin D binding protein (VDBP). The most common polymorphisms: rs4588 and rs7041 in the vitamin D binding protein gene may correlate with differences in vitamin D status in the serum. This review presents data that relate to the presence of genetic variants in the VDBP gene in correlation with certain diseases, mostly concerning cancers (breast, prostate, pancreatic, lung, colorectal, basal cell carcinoma cancer and cutaneous melanoma) or other related diseases (thyroid autoimmunity disorders, obesity, diabetes mellitus, bone metabolism, rheumatoid arthritis, ankylosing spondylitis, asthma, chronic obstructive pulmonary disease, tuberculosis and coronary artery diseases).